2022
DOI: 10.14814/phy2.15251
|View full text |Cite
|
Sign up to set email alerts
|

The ascending aorta of male hypertensive bicuspid aortic valve patients preferentially associated with a cellular aneurysmal phenotype

Abstract: This is an open access article under the terms of the Creative Commons Attribution License, which permits use, distribution and reproduction in any medium, provided the original work is properly cited.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 52 publications
0
2
0
Order By: Relevance
“…The results about sex disparity of MMP-2 in CVDs are conflicting and at variance with the considered condition. For instance, male patients affected by aneurysms have shown increased levels of MMP-2 in the aorta [ 90 ], a fact confirmed also in vivo in the mouse model [ 91 ] and in vitro on rat smooth muscle cells [ 92 ]. However, the opposite was found in females when considering patients with bicuspid valve thoracic aortic aneurysm (BV-AAA) [ 93 , 94 ].…”
Section: Sex Differences In Mmps and Pathologiesmentioning
confidence: 85%
See 1 more Smart Citation
“…The results about sex disparity of MMP-2 in CVDs are conflicting and at variance with the considered condition. For instance, male patients affected by aneurysms have shown increased levels of MMP-2 in the aorta [ 90 ], a fact confirmed also in vivo in the mouse model [ 91 ] and in vitro on rat smooth muscle cells [ 92 ]. However, the opposite was found in females when considering patients with bicuspid valve thoracic aortic aneurysm (BV-AAA) [ 93 , 94 ].…”
Section: Sex Differences In Mmps and Pathologiesmentioning
confidence: 85%
“…MMP-9 is far, together with MMP-2, the most studied metalloprotease in all aspects of CVDs, especially considering its connection with inflammation [ 105 ]. Most of the studies present in the literature have found an increase in the ascending aorta of male patients affected by aneurysms [ 90 , 93 , 106 ], with only one report finding the opposite result in females [ 91 ]. The former results are in large agreement with the clinical observation of a higher prevalence of aneurysms in males, making it a striking example of male disadvantage in CVDs [ 104 ].…”
Section: Sex Differences In Mmps and Pathologiesmentioning
confidence: 99%